Acute caffeine supplementation improves jumping, sprinting, and change-of-direction performance in basketball players when ingested in the morning but not evening. Issue 3 (4th March 2022) - Stojanović, Emilija; Scanlan, Aaron T.; Milanović, Zoran; Fox, Jordan L.; Stanković, Ratko; Dalbo, Vincent J.
ABSTRACT: This study compared the effects of acute caffeine supplementation (3 mg/kg) administered in the morning and evening on performance-related variables in basketball players. Eleven, national-level, adolescent male basketball players underwent field-based fitness testing on four occasions: morning (10:00) with caffeine ingestion (AMCAFF ), morning (10:00) with placebo ingestion (AMPLAC ), evening (21:00) with caffeine ingestion (PMCAFF ), and evening (21:00) with placebo ingestion (PMPLAC ). Fitness testing included of a countermovement jump without arm swing (CMJ), CMJ with arm swing (CMJAS), squat jump (SJ), Lane Agility Drill (LAD), 20-m linear sprint, and Suicide Run with (SRD) and without dribbling (SR). Data were analysed using two-way repeated measures analyses of variance and paired t-tests, with effect sizes (ES) also determined for all pairwise comparisons. Follow-up t-test comparisons revealed that AMCAFF produced small-moderate, significant ( p <0.001), improvements in CMJ (ES = 0.51), CMJAS (ES = 0.40), SJ (ES = 0.51), and SR (ES = −0.45) compared to AMPLAC. AMCAFF also produced a moderate, significantly ( p <0.001) faster LAD (ES = −0.61) compared to PMCAFF . PMPLAC demonstrated small-moderate, significant ( p <0.05) improvements in CMJ (ES = 0.43), CMJAS (ES = 0.48), and 20-m sprint (ES = −0.63) compared to AMPLAC . In contrast, AMPLAC resulted in large, significantly ( p <0.001), faster SRD (ES = −1.46) and SR (ES = −1.59) compared to PMPLAC . Given the ergogenic effects of caffeine during basketball-specific fitness tests appear to be influenced by time of ingestion, basketball practitioners should consider administering caffeine only to players in the morning to improve vertical jump, sprinting, and change-of-direction performance, with no beneficial effects observed with caffeine ingestion in the evening. Highlights The effect of caffeine supplementation on basketball-specific performance related variables were mediated by ingestion time in elite, adolescent basketball players. AMCAFF produced small-moderate improvements in vertical jump, change-of-direction, 20-m linear sprint, and repeated-sprint performance compared to AMPLAC while PMCAFF produced trivial differences in each performance-related variable compared to PMPLAC. Comparisons between ingestion times in the placebo condition revealed vertical jump height and 20-m sprint speed were impaired in the morning compared to the evening, but these time-dependent differences were eliminated when caffeine was consumed in the morning. Basketball practitioners should consider administering caffeine only to players in the morning to improve vertical jump, sprinting, and change-of-direction performance, with no beneficial effects observed with caffeine ingestion in the evening.